Adult Movement Pattern and Habitat Preferences of the Maghribian Endemic Gomphus lucasii (Odonata: Gomphidae). Issue 1 (28th October 2015) - Zebsa, Rabah; Khelifa, Rassim; Kahalerras, Amin
Abstract : The Algerian Cubtail ( Gomphus lucasii Selys) (Odonata: Gomphidae) is a river-dwelling dragonfly and one of the least known gomphid in the Palearctic. A survey of the movement patterns and habitat requirements of adults was conducted in the largest currently known population, located in the Seybouse River (Northeast Algeria). Daily mark-release-resighting surveys along a 2.5 km stretch of the watercourse and within plots in terrestrial habitats were carried out; a total of 1, 316 individuals were marked. The resighting rate along the watercourse was 8.13% and did not significantly vary with sex and age. Adult spatial distribution differed according to sex and age. Mature females were significantly further from the water than males. Mature males were observed not only along the watercourse but also far from the water, up to 450 m where reproductive pairs in copula were recorded. Preferred maturation and foraging sites were open grasslands and dense wheat fields. Philopatry to reproductive sites had a mean of 1.11%, while philopatry to emergence site was lower (0.4%) and noted only in males. The mean distance of natal dispersal (from emergence to reproductive areas) was 596.5 ± 4.94 m. The mean dispersal distance from one reproductive site to another was 180.97 ± 238.54 m. Both mature males and females preferred fast flowing water, but females were observed to oviposit in relatively small watercourses.